Development and Applicability Evaluation of a Pre-Hospital Patient/Injured Identification, Missing Search, and Tracking Software System in Disasters - Nurcan Esin; Deniz Acuner (Health and Technology Journal (HTechJ), 2025)
A disaster-response software system has been developed to minimize the risk of missing patients/injured individuals, infants, and children, and to track them during disasters. This study investigates the software's contributions to field use and healthcare personnel's triage experiences. Software has been developed based on contributions of 10 expert senior managers and assessed via Lawshe's technique; the Content Validity Index (CVI) is 0.988. Subsequently, 25 disaster-experienced healthcare workers from Istanbul's 112 Emergency Health Services station evaluated the system through semi-structured, in-depth interviews. Collected qualitative data were coded and analyzed using content analysis in MAXQDA 24. The research is organized into two themes—disaster software system and triage experiences—with subcodes. Findings show that triage depends not only on clinical knowledge but also on environmental conditions, social response, intra-team communication, and psychological factors. The disaster software supports triage by facilitating identification, patient tracking, acceleration of interventions, and data security. Integrated modules—such as QR codes, fingerprint, photo, and location—reduce healthcare personnel's workload and improve data accuracy. However, challenges include inadequate infrastructure, manual data entry burdens, mobile device incompatibility, and a lack of legal regulation. Suggested improvements by participants include integration with MERNİS (Turkey’s central population registry), voice command capability, barcode technology, and DNA-based modules. Overall, digital solutions can critically support triage in disaster settings operating within multidimensional dynamics.